Translation control in apoptosis - Liwak, U.; Faye, M.D.; Holcik, M. (Experimental Oncology, 2012)
Regulation of protein synthesis, although known for many decades, has only recently begun to be recognized as a critical control mechanism for the maintenance of cellular homeostasis and cellular stress response. One of the key advantages of translational control is the ability of cells to rapidly reprogram the protein output in response to internal or external triggers. This is particularly important during cellular response to stress that may lead to apoptosis by providing cells with a fine tuning mechanism that tips the balance between cell survival or apoptosis. In the following review we highlight several distinct mechanisms of translation control and provide specific examples of translational control during apoptosis. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.